Potential symmetries and new solutions of a simplified model for reacting mixtures - Senthilvelan, M.; Torrisi, M. (Iop Publishing Ltd, 2000)
In this paper, we investigate potential symmetries of a simplified model for reacting mixtures. We find new similarity reductions and wider class of solutions through this approach. Further, we explore an invertible mapping which linearizes the reacting mixture model.